Enhancement of photosensitivity in azo-epoxy resists for direct holographic recording - Mikelsone, Jelena; Teteris, Janis; Reinfelde, Mara (National Institute of Optoelectronics, 2019)
Azo-epoxy resist is promising material for direct holographic recording due to good photosensitivity and possibility to modify structure of molecule during synthesis – obtained polymer polymerization index easily can be changed by varying curing temperature and curing time. Produced photoresist had properties similar to low-weight molecular glasses. In this work 4-Aminoazobenze, Disperse Orange 2 and epoxy resin bisphenol A diglycidyl ether were used. Surface relief grating formation by direct holographic method was performed in obtained resi sts. Surface relief grating post-recording self-enhancement process was investigated. It allows to increase a depth of surface relief grating after holographic recording, using physical method – uniform light illumination. It decreases time and required exposure for recording, making holographic recording more effective because grating formation is less affected by vibrations and noises.
Financial support provided by Scientific Research Project for Students and Young Researchers Nr. SJZ/2017/7 realized at the Institute of Solid State Physics, University of Latvia is greatly acknowledged”
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Azo-epoxy films; Holographic recording; Surface relief grating